The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/bot.0b013e3182535f30
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tibiofibular Relationships at the Syndesmosis on Axial CT Imaging

Abstract: Measurements of tibiofibular relationships made on axial CT images are reliable. Because of significant anatomic variation between individuals, using a patient's contralateral ankle for comparison provides a precise definition of normal tibiofibular relationships. These criteria allow for the detection of subtle variations in the tibiofibular relationships indicating instability and provide a tool for postoperatively assessing the reduction of the injured syndesmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
137
3
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 52 publications
5
137
3
11
Order By: Relevance
“…Measurements were documented 1 cm above the centre of the tibial plafond. 8,12 Ratios were determined in order to assess the positional relationship of the tibia relative to the fibula. …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Measurements were documented 1 cm above the centre of the tibial plafond. 8,12 Ratios were determined in order to assess the positional relationship of the tibia relative to the fibula. …”
Section: Methodsmentioning
confidence: 99%
“…We have therefore described the anterior tibiofibular ratio (ATFR), which characterizes the ATFI:TW ratio described previously. It has been docu mented in the literature on a number of occasions that sagittal movement of the fibula relative to the tibia can represent a syndesmotic injury; 2,7,9,12,[16][17][18][19] however, to our knowledge only 2 studies 12,19 have attempted to determine specific criteria for diagnosis on the lateral view. In 2013, Grenier and colleagues 19 concluded that the tibiofibular joint can be accurately assessed on the lateral view when looking at the sagittal relationship of the tibia and the fibula.…”
Section: -11mentioning
confidence: 99%
See 3 more Smart Citations